Problematic of Public Budgeting Under Iraqi Legislation - عبد الله سلمان حسين; ياسين سناء احمد (Journal of Economics and Administrative Sciences, 2016)
The public budget in Iraq depends on a number of legislations across its fourth stages, starting from preparation to implementation and control; one of these legislations is the amended law of financial management and public Debt. No. (95) In 2004. Accordingly, the public budget cycle faces various failures, some of them resulted from the shortcomings in the legislation depended that effect on the public budget in a way or another; whereas the other failure resulted from no applying the legislation that adversely effect on the public budgeting stages that call for studying them and paying the attention toward them to present the suggestions that contribute in handling and developing public budgeting. The research has come out with the following recommendations that are: • Since (1921) the establishment of Iraq state, the economic and political transformations has played a great role in changing the legislative framework that govern the public budget cycle. • There is no legal framework can be depended on in achieving the various stages related to investing budget because the amended law financial management and public Debt. No. (95) In 2004 doesn’t pay sufficient attention for investing budget and for every things related the stages of investing budget cycle unlike the operative budget. • The use of items budget style in preparing public budget has caused the absence of objectives based on in process of public budget preparing and approving which is reflected on increasing public expenditures from a year to another, especially the operative ones. This is assured through analyzing the data of federal public budget for the years of 2009 till 2013, that is still without clear specific objectives to be reported and approved during the yearly public budget law; also this is reflected on public budget control which has been ignored through objectives implementation.